Pengaruh laju Pembebanan Organik Terhadap Efisiensi Penyisihan COD Limbah Cair Kelapa Sawit Menggunakan Bioeraktor Hibrid Anaerob Dua Tahap - Musfa, Nopi Andri; Ahmad, Adrianto; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The development of palm oil factories in the last few years the rapid growth experienced and gived the impact of positive and negative impact for the community. One of the positive impact is increasing foreign exchange and community welfare state, while the negative impact that is causing waste could reduce the quality of the environment. Characteristic of COD in the liquid waste of plant crude palm is 60.000 mg/l. The value of COD for is a measure of water pollution of organic substances naturally cannot be degradation with microbiologists process and may also result in reduced oxygen dissolved in water. COD handling of liquid waste from factories crude palm oil can be done in anaerobic two stages bioreactor hybrid use anaerobic. This research purposed to determine the effect of organic loading rate for efficiency of COD removal and determine the optimal organic loading rate for efficiency of COD removal on liquid waste oil palm treatment with using anaerobic bioreactor hybrids two stages. Operating conditions on this research that using room temperature, each bioreactor volume by 10 liters and feet flow rate in bioreactor I is 5 liters per day with organic loading rate by 30 kg COD/m3day. The result showed that an COD removal with varying the organic loading rate of 8,568 kgCOD/m3day, 12 kgCOD/m3day and 19,8 kgCOD/m3day, this result obtained the highest efficiency COD removal in the organic loading rate is 8,568 kgCOD/m3day with the equal is 93,06 %. This indicates that bioreactor anaerobic hybrid two stages are relatively better for COD removal from the liquid waste content of crude palm oil.   Keywords: Anaerobic, COD, Liquid Waste of Crude Palm Oil, Two-Stage Anaerobic Bioreactor Hybrid